Dielectric and piezoelectric properties of zirconium-doped bismuth sodium titanate ceramics - Watcharapasorn A. (2014)
Zirconium-doped bismuth sodium titanate ceramics were prepared using the conventional processing method. X-ray diffraction analysis indicated the materials were single phase with a systematic shift due to increased unit cell size. The measured densities and grain size of the ceramic samples were found to range from 5.79-6.03 g/cm3 and 0.5-1.6 μm, respectively. The dielectric constant as a function of temperature became broader as Zr content increased. The piezoelectric constant was found to decrease with increasing Zr. Within the range of the solid solutions investigated, the materials seem to be promising for high temperature applications where stable dielectric constant is required. © 2008 Trans Tech Publications, Switzerland.